UPAYA PENINGKATAN KINERJA KELOMPOK KERJA (POKJA) PEMILIHAN DENGAN METODE TENDER PADA PENGADAAN BARANG/JASA DI KABUPATEN PACITAN - Ulfah Suci Latifah; Syeh Assery (Jurnal Riset Mahasiswa, 2023)
The conditions in the Goods/Services Procurement Section of Pacitan Regency, especially the performance of the Selection Working Group still need to be optimized. This study aims to find out the causes of the performance of the election working group in Pacitan Regency which is still not optimal and to find out the efforts to improve the performance of the election working group in Pacitan Regency. The research in this thesis is a qualitative descriptive research. The informants in this study were the heads of the Pacitan Regency goods/services procurement department, commitment-making officials, selection working groups, SPSE admins and providers.The results showed that the performance of the election working group in Pacitan Regency was not optimal. This is due to several factors, namely changes in regulations, limited number of working group members, educational history of working groups who are not from Civil Engineering, easy tender requirements, intervention from several parties, server problems, slow internet network and working group personnel which is still new. While the efforts made to improve the working group's performance included involving the working group to technical guidance on procurement, conducting outreach regarding the procurement of goods/services, providing additional incentives for the working group, adding working group personnel, legal assistance from law enforcement officials, functioning servers and internet networks. well, training for working groups regarding system operation and construction service development from related agencies. Kondisi yang ada di Bagian Pengadaan Barang/Jasa Kabupaten Pacitan, khususnya kinerja Pokja pemilihan masih perlu dioptimalkan. Penelitian ini bertujuan untuk mengetahui penyebab kinerja pokja pemilihan di Kabupaten Pacitan yang masih belum optimal dan untuk mengetahui upaya-upaya guna meningkatkan kinerja pokja pemilihan di Kabupaten Pacitan.Penelitian dalam tesis ini merupakan penelitian deskriptif kualitatif. Informan dalam penelitian ini adalah kepala bagian pengadaan barang/jasa Kabupaten Pacitan, Pejabat pembuat komitmen, pokja pemilihan, admin SPSE dan penyedia.Hasil penelitian menunjukan bahwa kinerja pokja pemilihan di Kabupaten Pacitan belum optimal. Hal ini dikarenakan oleh beberapa factor, yaitu Perubahan peraturan, jumlah anggota pokja yang terbatas, riwayat pendidikan pokja yang bukan berasal dari Teknik Sipil, persyaratan tender yang mudah, adanya intervensi dari beberapa pihak, server yang mengalami gangguan, jaringan internet yang lambat dan personil pokja yang masih baru. Sedangkan upaya-upaya yang dilakukan auntuk meningkatkan kinerja pokja diantaranya adalah mengikutsertakan pokja ke bimbingan teknis mengenai pengadaan, melakukan sosialisasi mengenai pengadaan barang/jasa, diberikannya insentif tambahan untuk pokja, penambahan personil pokja, pendampingan hukum dari aparat penegak hokum, server dan jaringan internet berfungsi dengan baik, pelatihan kepada pokja mengenai pengoperasian sistem dan pembinaan jasa konstruksi dari Dinas terkait.